Unstable grounds: Investigating ulterior spaces for practising. (1st June 2013) - Robbins, Felix
This article investigates alternative ways of working. It is a reflection on the contradictions of architectural practice and the opportunities for design that acknowledges these contradictions productively. The article continues an investigation into the construction of an architectural project – the contradictory requirements for the 'construction' of architecture and the opportunities in dissolving these requirements by design. It develops as an enquiry into the possibilities of actively acknowledging the contradictions and ambiguities of the discipline as a means to go on, as well as design that operates within the slippages, translations and movements between the 'construction of a project' to tentatively speculate on alternative and temporary locations and spaces of practice. It elaborates on ongoing design work of a 'dwelling' and the explicit processes, choices and techniques that move between the construction of narrative, site, material and space/time. The article argues that the discipline of architecture is unavoidably ungrounded – with the relevance and approach to practising lying exposed within the wider context of cultural production and a 'deluge' of multiple and relative shifting landscapes of 'project'. It argues, however, that this does not justify merely reconstructing the grounds of the discipline in other terms – whether that be nostalgic, technological or superficial. Instead, it argues that other spaces for practising must be inhabited – spaces that make use of the 'deluge' and the ambiguities of practice and suggest alternative approaches to understanding and creating a sufficiency and productivity of making architecture.